ANALISIS KESALAHAN KONSEP GENETIKA PADA SOAL UJI KOMPETENSI SERTIFIKASI GURU DALAM JABATAN TAHUN 2012 - Chumidach Roini; Suparman Suparman; Zulkifli Ahmad (Universitas Sebelas Maret, 2014)
The research was conducted to descript misconception and other mistake in genetics concept. The Method: by using the document of teacher competency testing 2012 Number 190-51 to analyze about the questions and the answers that related to genetics concept. After scrutinizing, each number is judged. The result revealed there are 11 questions related to genetic and four of them are good question, seven of them are incorrect include unclear questions, miss concept and do not have right answer. Keywords: misconception in genetic, teacher competency testing